Method for generating molybdenum dioxide or molybdenum carbide through reduction of molybdenum trioxide and application

By synthesizing spherical molybdenum-based precursors with molybdenum trioxide and calcining at low temperature, the problem of slow lithiation reaction caused by high crystallinity of molybdenum dioxide materials was solved, and MoO2/C and Mo2C/C materials with excellent electrochemical properties were prepared, which were suitable for lithium-ion battery negative electrode materials.

CN119706941AActive Publication Date: 2025-03-28RESEARCH INSTITUTE OF TSINGHUA UNIVERSITY IN SHENZHEN

Patent Information

Application Number
CN202411941806.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the high crystallinity of molybdenum dioxide (MoO2) material leads to slow lithiation reaction, and the molybdenum-oxygen bond cannot be sufficiently broken in the low potential range, resulting in capacity attenuation.

Method used

Molybdenum trioxide (MoO3) is used as the molybdenum source, and spherical molybdenum-based precursor (H0.93MoO3/C) is synthesized through microwave-assisted solvent thermal reaction, and calcined at low temperature in an argon or hydrogen argon plasma atmosphere to produce molybdenum dioxide or molybdenum carbide (MoO2/C or Mo2C/C) materials.

Benefits of technology

The preparation of high-active, uniform micro-spherical MoO2/C and Mo2C/C materials has been achieved, with good electrochemical properties, including single-electron insertion/detachment and quad-electron conversion reaction activities, and is suitable as the negative electrode material for lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706941A_ABST
    Figure CN119706941A_ABST
Patent Text Reader

Abstract

The invention provides a method for generating molybdenum dioxide or molybdenum carbide through reduction of molybdenum trioxide and application, and the method comprises the following steps: dispersing MoO3 powder in a mixed solution of monohydric alcohol and polyhydric alcohol, adding a triblock copolymer P123 stabilizer, carrying out microwave-assisted solvothermal reaction on the obtained suspension, centrifuging or filtering and washing to obtain molybdenum dioxide or molybdenum carbide; the obtained brown H0. 93MoO3 / C precursor microspheres are placed in an argon plasma environment, high-temperature calcination is carried out at the temperature of 500-600 DEG C for 30-60 min, and brown black MoO2 / C microspheres are obtained; or placing the H0. 93MoO3 / C precursor in a hydrogen-argon plasma environment, and calcining the H0. 93MoO3 / C precursor at a high temperature of 500-600 DEG C for 30-60 minutes to obtain the gray Mo2C / C microspheres. The MoO2 / C and Mo2C / C materials prepared in the invention have nanocrystalline characteristics and excellent electrochemical performance, and have good commercial application prospects as lithium battery negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery materials, and in particular to a method and application of preparing a spherical molybdenum-based precursor by reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide. Background Art

[0002] Transition metal oxides (TMOs) exhibit diverse lithiation reaction mechanisms due to the rich and varied valence states of transition elements and their unique crystal structures. They are expected to replace graphite and become a promising electrode active material for lithium-ion batteries. Among them, TMOs in the front subgroups (IVB and VB) (including TiO2, V2O5, and Nb2O5, etc.) have stable crystal structures that can achieve reversible insertion / extraction of lithium ions in the structure; TMOs in the rear subgroups (VIII and IB) (including FeO, CoO, Co3O4, NiO, Cu2O, etc.) only exhibit multi-electron conversion reaction-type lithiation activity at the nanoscale; while TMOs in the intermediate subgroups (VIB and VIII) (including MoO3, RuO2, MoO2, etc.) exhibit lithiation activity at higher potential ranges (>1.00V). vs. Li / Li⁺) exhibits reversible insertion / extraction. vs. Li / Li⁺) is a multi-electron conversion reaction that exhibits gradual amorphization. Currently, molybdenum dioxide (MoO2) with high theoretical capacity (838 mAh g⁻¹) and metallic conductivity has attracted widespread attention. However, the application of commercial bulk MoO2 is limited, mainly because the monoclinic-orthorhombic-monoclinic phase transition of the distorted rutile crystal structure during lithium ion insertion / removal under high crystallinity conditions is a phase transition with slow lithiation reaction, which hinders further lithiation reaction and is manifested as a slow lithiation reaction in the lower potential range (<1.00 V). vs. Li / Li⁺) cannot fully break the Mo-O bond to trigger the multi-electron conversion reaction, and will produce cumulative volume changes during the lithiation process, showing an activation process with a long number of cycles, followed by severe capacity decay. Therefore, nano-scaling of the microstructure and micro-crystallization of crystalline materials are considered to be effective strategies to overcome the limitations of MoO2 bulk materials when used as negative electrode materials for lithium-ion batteries.

[0003] Many studies have focused on designing and preparing efficient nanostructures, aiming to expand the reaction contact surface, shorten the ion diffusion path and reduce internal stress. Porous MoO2@C nanooctahedra can be derived from metal organic frameworks (MOFs) of polyoxometalates; while ordered mesoporous MoO2 can be precisely synthesized by sacrificial template method, such as introducing ordered mesoporous carbon CMK-3, through controlled molybdate impregnation process and carbon thermal reduction conditions. Through chelation and subsequent carbonization process, 3D hierarchical MoO2 nanospheres can be prepared, in which amorphous carbon matrix self-assembles. Two-dimensional MoO2 flakes can be prepared by self-assembly using salt, glucose or surfactant as template. The one-dimensional MoO2 nanobelt structure can be retained by carbon coating the surface of the precursor MoO3 nanobelt and then reducing it; otherwise, nanoparticles are obtained. The above nanomaterials all have high specific surface area, which is conducive to the diffusion and embedding of lithium ions, and show good rate and cycle stability performance, but at the same time, they may increase interfacial resistance and side reactions, and the first-cycle coulomb efficiency is low.

[0004] The regulation of the microcrystallization of crystalline materials is mainly achieved by attaching molybdenum-based precursors to amorphous carbon matrices and selecting the calcination temperature or time after self-assembly to control the recrystallization of MoO2, aiming to weaken the restriction of the distorted rutile crystal structure on the lithium-rich state conversion reaction, break the molybdenum-oxygen bond (Mo-O bond), and achieve rapid excitation of four-electron complete conversion reaction through the nanocrystal effect. However, when using nano-MoO3 as a precursor, it is still necessary to react at a temperature greater than 680°C to obtain a high-crystallinity MoO2 material; if molybdenum polyoxometalates or organic chelated ligands are used as precursors, it is necessary to react at a temperature greater than 600°C to obtain a MoO2 material with a high crystallinity and high carbon content. The above methods also have the defects of unstable crystallinity and product size, which limits the commercial application of materials.

[0005] In addition, transition metal carbides (TMCs) have the characteristics of high conductivity, good chemical stability and inherent catalytic activity, and have been widely studied and used as active materials in various energy storage fields. Among them, Mo2C, which is etched by MAX or carbothermally reduced in H2 / Ar atmosphere, has a higher energy storage capacity than Nb2C (about 250 mAh g -1 )、V2C(about 260 mAh g -1 ) and Ti2C (about 160 mAh g -1 ), showing a higher capacity (about 300 mAh g -1 ) and gradually increasing cycle performance (capacity retention rate > 100%). However, Mo2C materials need to be reduced by carbon thermal reduction at a temperature greater than 800°C, which is harsh and energy-intensive. Moreover, high-temperature reactions can only obtain Mo2C with extremely high crystallinity, and it is impossible to achieve microcrystallization regulation of this type of material. Summary of the invention

[0006] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art. Firstly, a method for preparing a spherical molybdenum-based precursor by reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide is provided.

[0007] The method provided in this application comprises the following steps:

[0008] S1 MoO3 powder was stirred and dispersed in a mixed solution of monohydric alcohol and polyhydric alcohol, and then triblock copolymer P123 stabilizer was added. The resulting suspension was subjected to microwave-assisted solvent thermal reaction, and then centrifuged or filtered and washed to obtain brown H with a diameter of 1.50-1.60 μm. 0.93 MoO3 / C precursor microspheres;

[0009] S2: H obtained in step S1 0.93 The MoO3 / C precursor is placed in an argon plasma atmosphere and calcined at a high temperature of 500-600°C for 30-60 min to obtain brown-black MoO2 / C microspheres with a diameter of 1.00-1.10 μm. Alternatively, the H obtained in step S1 0.93 The MoO3 / C precursor is placed in a hydrogen-argon plasma atmosphere and calcined at a high temperature of 500-600°C for 30-60 minutes to obtain dark grey Mo2C / C microspheres with a diameter of 0.75-0.85 μm.

[0010] The present application also provides the use of the MoO2 / C material and Mo2C / C material prepared by the above method in negative electrode materials for lithium-ion batteries.

[0011] This application has the following technical effects:

[0012] (1) This application uses commercial MoO3 as a heterogeneous molybdenum source, without the need to introduce an additional carbon source as a reducing agent, and can directly synthesize highly active, uniform micron-shaped spherical H 0.93 MoO3 / C precursor, and through H 0.93 The MoO3 / C precursor is calcined at low temperature, and the calcination temperature is controlled and combined with argon plasma or hydrogen-argon plasma reducing atmosphere to fully reduce and synthesize MoO2 / C material and Mo2C / C material. The method is simple and low in cost.

[0013] (2) This application introduces the triblock copolymer P123 stabilizer to avoid the collapse or adhesion of the microsphere structure obtained by microwave-assisted solvent thermal reaction due to the deviation of the mixing volume ratio of the dispersed solution of monohydric alcohol and polyhydric alcohol, effectively ensuring H 0.93The diameter of the MoO3 / C precursor microspheres is in the range of 1.50-1.60μm, the diameter of the MoO2 / C material microspheres is in the range of 1.00-1.10μm, and the diameter of the Mo2C / C material microspheres is in the range of 0.75-0.85μm. The products have high consistency, and the structure of the prepared materials is stable, the surface is negatively charged, and they all have good monodisperse characteristics.

[0014] (3) The MoO2 / C material and Mo2C / C material prepared in this application both have nanocrystalline characteristics. The MoO2 / C material has a high conductivity at 1.00-3.00 V ( vs. Li / Li + ) potential range, showing single electron insertion / extraction lithium storage activity; in the range of 0.01~3.00 V ( vs. Li / Li + ) potential range, it shows four-electron conversion reaction lithium storage activity, Mo2C / C material in the range of 0.01~3.00 V ( vs. Li / Li + ) potential range, the surface lithium atom adsorption and desorption and the gradual conversion reaction lithium storage activity are exhibited, both of which have excellent electrochemical properties. The introduction of MoO2 / C and Mo2C / C as negative electrode materials for lithium batteries has good commercial application prospects and provides a new economical and effective way for the preparation of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the MoO3 block in Example 1, H 0.93 X-ray diffraction patterns of MoO3 / C precursor, MoO2 / C and Mo2C / C materials;

[0016] Figure 2 is H in Example 1 0.93 Particle size distribution curves of MoO3 / C precursor, MoO2 / C and Mo2C / C materials;

[0017] Figure 3 is H in Example 1 0.93 Zeta potential distribution curves of MoO3 / C precursor, MoO2 / C and Mo2C / C materials;

[0018] Figure 4 is H in Example 1 0.93 Scanning electron micrographs of MoO3 / C precursor, MoO2 / C and Mo2C / C materials;

[0019] Figure 5 is H in Example 1 0.93 EDS spectrum of MoO3 / C precursor;

[0020] Figure 6 Cyclic voltammetry curves of MoO2 / C and Mo2C / C materials in Example 1;

[0021] Figure 7 The charge and discharge rate performance curves of MoO2 / C and Mo2C / C materials in Example 1;

[0022] Figure 8 The electrochemical impedance spectroscopy of the MoO2 / C and Mo2C / C materials in Example 1 after 20 charge and discharge cycles;

[0023] Fig. 9 is the X-ray diffraction pattern of the precursor obtained in Comparative Example 1;

[0024] Fig.10 is the X-ray diffraction pattern of the precursor obtained in Comparative Example 2;

[0025] Fig.11 This is the X-ray diffraction pattern of the precursor obtained in Comparative Example 3;

[0026] Fig.12 This is a scanning electron microscope photograph of the precursor obtained in Comparative Example 3;

[0027] Fig.13 This is a scanning electron microscope photograph of the precursor obtained in Comparative Example 4;

[0028] Fig.14 The X-ray diffraction pattern of the MoO2 / C material obtained in Comparative Example 5;

[0029] Fig.15 This is the X-ray diffraction pattern of the Mo2C / C material obtained in Comparative Example 6. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0031] The present application provides a method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide, comprising the following steps:

[0032] S1 MoO3 powder was stirred and dispersed in a mixed solution of monohydric alcohol and polyhydric alcohol, and then a triblock copolymer P123 stabilizer was added. The resulting suspension was subjected to microwave-assisted solvent thermal reaction, and then centrifuged or filtered and washed to obtain brown H with a diameter of 1.50-1.60 μm. 0.93 MoO3 / C precursor microspheres have good monodispersity in water.

[0033] In this step, the MoO3 powder is stirred and dispersed in the mixed solution of the monohydric alcohol and the polyhydric alcohol, so that the MoO3 is evenly dispersed in the mixed solution to form a suspension, and the reduction reaction activity of the system is enhanced, so that the MoO3 can be completely converted into H 0.93 MoO3 / C precursor. Moreover, amorphous carbon can be derived from the microwave-assisted solvent thermal decomposition products of monohydric alcohols and dihydric alcohols, so the present application does not need to introduce an additional carbon source as a reducing agent. Adding a triblock copolymer P123 stabilizer to the mixed solution can maintain the material morphology and prevent particle agglomeration, avoid the collapse of the micron sphere structure caused by the actual volume ratio deviation in the mixed solution of monohydric alcohols and polyhydric alcohols, and ensure that the final MoO2 / C and Mo2C / C products are within the set size range, and the prepared material structure is stable, the surface is negatively charged, and has good monodisperse characteristics, which improves the processability of mixed pulping and uniform coating during the preparation of subsequent lithium-ion battery products, and can also improve the tap density and electrolyte permeability.

[0034] The monohydric alcohol is selected from at least one of methanol, ethanol and isopropanol, preferably isopropanol; the polyhydric alcohol is selected from at least one of ethylene glycol and glycerol, preferably glycerol.

[0035] Wherein, the volume ratio of monohydric alcohol to polyhydric alcohol is 1:2 to 2:1.

[0036] The mass ratio of the added amount of the triblock copolymer P123 stabilizer to the mixed solution of the monohydric alcohol and the polyhydric alcohol is: 10g-30g / L, preferably 20g / L.

[0037] The microwave-assisted solvent thermal reaction temperature is 180-210° C., preferably 200° C., and the insulation time is 20-40 min, preferably 30 min.

[0038] S2: H obtained in step S1 0.93 The MoO3 / C precursor was placed in an argon plasma atmosphere and calcined at a reaction temperature of 500-600°C for 30-60 min to obtain brown-black MoO2 / C microspheres with a diameter of 1.00-1.10 μm. Alternatively, the H obtained in step S1 0.93 The MoO3 / C precursor is placed in a hydrogen-argon plasma atmosphere and calcined at a reaction temperature of 500-600°C for 30-60 min to obtain dark grey Mo2C / C microspheres with a diameter of 0.75-0.85 μm.

[0039] The reaction temperature is preferably 600° C., the calcination time is preferably 40 min, and the hydrogen in the hydrogen-argon plasma is 15% of the total amount.

[0040] The MoO2 / C material prepared by the above method is a microcrystalline material with a microscopic spherical structure. When used as a negative electrode material for lithium-ion batteries, its secondary micron-sphere structure can well adapt to the volume expansion caused by the lithiation process. The micron-sphere structure can reduce the interface resistance and side reactions to improve the first-cycle coulomb efficiency. The nano-microcrystalline structure can shorten the activation period of the four-electron conversion reaction. MoO2 / C material has a high conductivity at 1.00-3.00 V ( vs. Li / Li + ) potential range, showing single electron insertion / extraction lithium storage activity; in the range of 0.01~3.00 V ( vs. Li / Li + ) potential range, it exhibits four-electron conversion reaction lithium storage activity and excellent electrochemical performance.

[0041] The prepared Mo2C / C material has nanocrystalline characteristics. As a lithium-ion negative electrode material, it has good rate and long cycle stability in the range of 0.01 to 3.00 V ( vs. Li / Li + ) potential range, the surface lithium atoms show adsorption and desorption and the gradual conversion reaction lithium storage activity, and the electrochemical performance is excellent.

[0042] The present application also provides the application of MoO2 / C and Mo2C / C materials in lithium-ion batteries.

[0043] MoO2 / C microcrystalline material with a microscopic spherical structure is used as a lithium-ion negative electrode material. Its secondary micron-sphere structure can well adapt to the volume expansion caused by the lithiation process. The micron-sphere structure can reduce the interface resistance and side reactions and improve the first-cycle coulomb efficiency. The nano-microcrystalline structure can shorten the activation cycle of the four-electron conversion reaction.

[0044] Using Mo2C / C microcrystalline material with a microscopic spherical structure as a lithium-ion negative electrode material has good rate performance and long cycle stability.

[0045] The present application applies MoO2 / C and Mo2C / C materials to lithium-ion batteries, which reduces the manufacturing cost of lithium-ion batteries and improves the electrochemical performance of lithium-ion batteries.

[0046] The MoO2 / C and Mo2C / C materials of the present application are used as the active materials of the negative electrode materials of lithium-ion batteries to prepare the process of lithium-ion half-cells:

[0047] (1) Grinding MoO2 / C or Mo2C / C material, conductive agent acetylene black, and adhesive polyvinylidene fluoride (PVDF) in a weight ratio of 8:1:1 for 30 min to mix them evenly, and dispersing them in N-methylpyrrolidone (NMP) solution to prepare slurry;

[0048] (2) The slurry is evenly coated on the copper foil by a coating machine, and vacuum dried at 110°C for 12 hours, and cut into circular electrodes with a diameter of 16 mm by a cutting machine;

[0049] (3) The assembly of the CR2032 button half-cell was carried out in a glove box filled with high-purity argon:

[0050] Place a gasket and spring in the negative electrode shell, place a metal lithium sheet with a diameter of 16 mm on the gasket, use a pipette to drip electrolyte (1M LiPF6 dissolved in ethyl carbonate (EC) / dimethyl carbonate (DMC) with a volume ratio of 1:1), place a circular polypropylene diaphragm with a diameter of 19 mm, then drip electrolyte with a pipette, place the cut electrode as the counter electrode, and finally encapsulate the button battery.

[0051] The method of reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide in the present application is further described in detail below in conjunction with specific embodiments.

[0052] Embodiment 1:

[0053] S1 100 g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 500 mL of isopropanol and 500 mL of glycerol, and then 20 g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, and microwave-assisted solvent thermal reaction was carried out at a reaction temperature of 200 ° C for 30 min. The mixture was centrifuged or filtered, and washed with three distilled water and two ethanol to obtain a brown H 0.93 MoO3 / C precursor;

[0054] S2 H 0.93 The MoO3 / C precursor was placed in an argon plasma atmosphere and calcined at 600°C for 40 min to obtain the MoO2 / C material; H 0.93 The MoO3 / C precursor was placed in a 15% hydrogen-argon plasma atmosphere and calcined at 600°C for 40 min to obtain the Mo2C / C material.

[0055] See also Figure 1 In this Example 1, commercial MoO3 powder is mixed with isopropanol, glycerol, and triblock copolymer P123 stabilizer, and microwave-assisted solvent thermal reaction can be completely converted into H 0.93 MoO3 / C precursor, no other impurity phase; H 0.93 The MoO3 / C precursor is placed in argon plasma and calcined at low temperature, which can completely reduce it to MoO2 / C material without other impurity phases. 0.93 When the MoO3 / C precursor is calcined in a 15% hydrogen-argon plasma atmosphere, it can be completely converted from H 0.93MoO3 / C is fully reduced to Mo2C / C material without other impurity phases.

[0056] Figure 2 The results showed that the obtained H 0.93 The particle size distribution of MoO3 / C precursor, MoO2 / C and Mo2C / C materials shows a sharp single peak, with good particle uniformity. Figure 2 and Figure 4 The results showed that H 0.93 The MoO3 / C precursor is a micron sphere with a diameter of about 1.50 μm, the MoO2 / C material is a micron sphere with a diameter of about 1.00 μm, and the Mo2C / C material is a micron sphere with a diameter of about 0.80 μm.

[0057] from Figure 3 It can be seen that the H obtained in this embodiment 0.93 The Zeta potential distribution of MoO3 / C precursor, MoO2 / C and Mo2C / C materials is a single negative peak, which has good monodispersity in the aqueous phase and has a negative charge on the surface. 0.93 The MoO3 / C precursor is -58.7 mV, the MoO2 / C material is -49.3 mV, and the Mo2C / C material is -39.2 mV.

[0058] Figure 5 The results showed that the obtained H 0.93 The mass percentages of Mo, O, and C in MoO3 / C are 56.18%, 25.71%, and 40.74%, respectively. 0.93 The source of amorphous carbon in MoO3 / C precursor is mainly the decomposition products of monohydric alcohols and polyhydric alcohols during microwave-assisted solvothermal treatment.

[0059] The obtained MoO2 / C and Mo2C / C materials were assembled into button-type lithium-ion half-cells, and the electrochemical properties were tested. Figure 6 The results show that in the range of 1.00~3.00 V( vs. Li / Li + ) potential range, MoO2 / C exhibits single-electron insertion / extraction lithium storage activity, while Mo2C / C exhibits reversible adsorption / desorption activity; in the range of 0.01 to 3.00 V ( vs. Li / Li + ), MoO2 / C exhibits a four-electron conversion reaction lithium storage activity, while Mo2C / C exhibits lithium atom adsorption and desorption and gradual conversion reaction activity.

[0060] from Figure 7 It can be seen that in the range of 1.00 to 3.00 V ( vs. Li / Li +) potential interval, current density 100 mA g -1 The capacity of MoO2 / C is about 149.1 mAh g -1 The first cycle coulombic efficiency is 63.2% and the current density is 500 mA g -1 The capacity of MoO2 / C is about 89.8 mAh g -1 ; 0.01~3.00 V( vs. Li / Li + ) potential interval, current density 100 mA g -1 The capacity of MoO2 / C is about 833.6 mAh g -1 The first cycle coulombic efficiency is 78.2% and the current density is 1000 mA g -1 The capacity of MoO2 / C is about 666.2 mAh g -1 ; 0.01~3.00 V( vs. Li / Li + ) potential interval, current density 100 mA g -1 The capacity of Mo2C / C is about 259.1 mAh g -1 The first cycle coulombic efficiency is 51.2% and the current density is 1000 mA g -1 The capacity of Mo2C / C is about 104.3 mAh g -1 .

[0061] Figure 8 The results show that after 20 cycles of charge and discharge, the EIS in the high-frequency band is an arc, corresponding to the electrochemical reaction impedance. The comprehensive impedance of MoO2 / C is about 120Ω, and the comprehensive impedance of Mo2C / C is about 60Ω, indicating that both have the conductive characteristics of their parent metals; the low-frequency band is a slant line, corresponding to the diffusion behavior of lithium ions in the solid phase, and both have good Warburg diffusion characteristics.

[0062] Therefore, as a single electron insertion / extraction type lithium battery anode material, the electrochemical performance of MoO2 / C is equivalent to that of commercial Li4Ti5O 12 Materials (theoretical capacity 175 mAh g -1 ), which has a richer charge and discharge platform and pseudocapacitive characteristics; as a negative electrode material for multi-electron conversion reaction lithium batteries, the electrochemical performance of MoO2 / C is better than that of commercial artificial graphite materials (theoretical capacity 372 mAh g -1 ), which has a higher specific capacity than it; as a new type of lithium battery negative electrode material, Mo2C / C has better rate performance than commercial artificial graphite materials and can adapt to the characteristics of fast charging and discharging.

[0063] Embodiment 2:

[0064] S1 100g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 350mL of isopropanol and 650mL of glycerol, and then 25g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, and microwave-assisted solvent thermal reaction was carried out at 180℃ for 20min. The suspension was centrifuged or filtered, and washed with three distilled water and two ethanol to obtain a brown H 0.93 MoO3 / C precursor;

[0065] S2 H 0.93 The MoO3 / C precursor was placed in an argon plasma atmosphere and calcined at 500°C for 30 min to obtain a brown-black MoO2 / C material. The obtained H 0.93 The MoO3 / C precursor was placed in a 15% hydrogen-argon plasma atmosphere and calcined at 500°C for 30 min to obtain a dark grey Mo2C / C material.

[0066] After testing, the H obtained in this embodiment 0.93 The MoO3 / C precursor is a microsphere with a diameter of 1.60 μm, the MoO2 / C material is a microsphere with a diameter of 1.10 μm, and the Mo2C / C material is a microsphere with a diameter of 0.85 μm, all of which have negative charges on their surfaces.

[0067] Embodiment 3:

[0068] S1 100g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 650mL of isopropanol and 350mL of glycerol, and then 30g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, and microwave-assisted solvent thermal reaction was carried out at a reaction temperature of 210℃ for 40min. The mixture was centrifuged or filtered, and washed with three distilled water and two ethanol to obtain a brown H 0.93 MoO3 / C precursor;

[0069] S2 H 0.93 The MoO3 / C precursor was placed in an argon plasma atmosphere and calcined at 600°C for 60 min to obtain a brown-black MoO2 / C material. The obtained H 0.93 The MoO3 / C precursor was placed in a 10% 15% hydrogen-argon plasma atmosphere and calcined at 600°C for 60 min to obtain a dark grey Mo2C / C material.

[0070] After testing, the H obtained in this embodiment 0.93The MoO3 / C precursor is a microsphere with a diameter of 1.60 μm, the MoO2 / C material is a microsphere with a diameter of 1.05 μm, and the Mo2C / C material is a microsphere with a diameter of 0.78 μm, all of which have negative charges on their surfaces.

[0071] Embodiment 4:

[0072] S1 100g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 600mL of methanol and 400mL of ethylene glycol, and then 10g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor for microwave-assisted solvent thermal reaction, kept at a reaction temperature of 180℃ for 30 min, centrifuged or filtered, washed with three distilled water and two ethanol, and a brown H 0.93 MoO3 / C precursor;

[0073] S2 will obtain H 0.93 The MoO3 / C precursor was calcined at 600℃ for 50min under argon plasma atmosphere to obtain brown-black MoO2 / C material. The obtained H 0.93 The MoO3 / C precursor was placed in a 15% hydrogen-argon plasma atmosphere and calcined at 600°C for 50 min to obtain a dark grey Mo2C / C material.

[0074] After testing, the H obtained in this embodiment 0.93 The MoO3 / C precursor is a microsphere with a diameter of 1.55μm, the MoO2 / C material is a microsphere with a diameter of 1.05μm, and the Mo2C / C material is a microsphere with a diameter of 0.85μm, all of which have negative charges on their surfaces.

[0075] Embodiment 5:

[0076] S1 100g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 350mL of ethanol and 650mL of glycerol, and then 20g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, and microwave-assisted solvent thermal reaction was carried out at a reaction temperature of 180℃ for 30 min. The mixture was centrifuged or filtered, and washed with three distilled water and two ethanol to obtain a brown H 0.93 MoO3 / C precursor;

[0077] S2 will obtain H 0.93 The MoO3 / C precursor was placed in an argon plasma atmosphere and calcined at a reaction temperature of 500°C for 40 min to obtain a brown-black MoO2 / C material. The obtained H 0.93The MoO3 / C precursor was placed in a 15% hydrogen-argon plasma atmosphere and calcined at a reaction temperature of 500°C for 40 min to obtain a dark gray Mo2C / C material.

[0078] After testing, the H obtained in this embodiment 0.93 The MoO3 / C precursor is a micron sphere with a diameter of 1.55 μm, the MoO2 / C material is a micron sphere with a diameter of 1.05 μm, and the Mo2C / C material is a micron sphere with a diameter of 0.75 μm, all of which have negative charges on their surfaces.

[0079] Embodiment 6:

[0080] S1 100g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 350mL of ethanol and 650mL of ethylene glycol, and then 25g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, and microwave-assisted solvent thermal reaction was carried out at a reaction temperature of 190℃ for 40 min. The mixture was centrifuged or filtered, and washed with three distilled water and two ethanol to obtain a brown H 0.93 MoO3 / C precursor;

[0081] S2 will obtain H 0.93 The MoO3 / C precursor was placed in an argon plasma atmosphere and calcined at a reaction temperature of 550°C for 60 min to obtain a brown-black MoO2 / C material. The obtained H 0.93 The MoO3 / C precursor was placed in 15% hydrogen-argon plasma and calcined at 550°C for 60 min to obtain a dark grey Mo2C / C material.

[0082] After testing, the H obtained in this embodiment 0.93 The MoO3 / C precursor is a microsphere with a diameter of 1.60 μm, the MoO2 / C material is a microsphere with a diameter of 1.08 μm, and the Mo2C / C material is a microsphere with a diameter of 0.82 μm, all of which have negative charges on their surfaces.

[0083] Comparative Example 1:

[0084] 100 g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 500 mL of isopropanol and 500 mL of propylene glycol, and 20 g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor and subjected to microwave-assisted solvent thermal reaction. The insulation time was fixed at 30 min, and the reaction temperatures were controlled at 140°C, 160°C, and 220°C, respectively. After centrifugation or filtration, the mixture was washed three times with distilled water and twice with ethanol to obtain a precursor.

[0085] Fig. 9The results show that during the microwave-assisted solvothermal reaction, when the temperature is lower than 160 °C, the obtained product is mainly amorphous. 0.93 MoO3 phase has not yet crystallized; when the temperature is higher than 220℃, H 0.93 The MoO3 phase has a clear X-ray diffraction peak, which means that as the temperature rises, the crystallinity of the material further increases, and there are no other impurity phases. However, the higher temperature microwave-assisted solvothermal reaction has high requirements for equipment, high energy consumption, and safety issues such as microwave leakage.

[0086] Comparative Example 2:

[0087] 100 g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 500 mL of isopropanol and 500 mL of propylene glycol, and 20 g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor and subjected to microwave-assisted solvent thermal reaction. The reaction temperature was fixed at 200°C, and the insulation time was controlled to be 120 min, 150 min, and 180 min respectively. After centrifugation or filtration, the mixture was washed three times with distilled water and twice with ethanol to obtain a precursor.

[0088] Fig.10 The results show that in the microwave-assisted solvothermal reaction process, H with higher crystallinity can be obtained by prolonging the holding time at 200 °C. 0.93 MoO3 / C precursor, without other impurity phases, is only used as a secondary recrystallization of minerals. However, the advantage of microwave-assisted solvothermal reaction is that it can greatly shorten the time required for mineralization crystallization of traditional solvothermal reaction. Longer time requires high equipment requirements, high energy consumption, and there are safety issues such as microwave leakage.

[0089] Comparative Example 3:

[0090] 100 g of commercial MoO3 powder was stirred and dispersed in 1000 mL of isopropanol solution or 1000 mL of glycerol solution, that is, 100% isopropanol and 100% glycerol, and 20 g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, subjected to microwave-assisted solvent thermal reaction, and kept warm at a reaction temperature of 200°C for 30 min. After centrifugation or filtration, it was washed three times with distilled water and twice with ethanol to obtain a precursor.

[0091] Fig.11 The results show that MoO3 can be obtained by high temperature reaction in isopropanol solution. 3-x phase, and the MoO3 phase is still partially retained, indicating that the high-temperature thermal reduction reaction of MoO3 in isopropanol solvent is insufficient and is not a necessary condition for the synthesis of MoO3; while MoO3 obtains H after high-temperature reaction in propylene glycol solution. 0.93 The MoO3 phase and the absence of other impurity phases indicate that the high-temperature thermal reduction of MoO3 by glycerol is sufficient.0.93 Therefore, the ratio of the components of the mixed solution in the microwave-assisted solvothermal reaction directly determines the H 0.93 Transformation of MoO3 phase.

[0092] Fig.12 The results show that the precursor obtained by microwave-assisted solvothermal reaction with 100% isopropanol solvent still retains the bulk structure of MoO3, which also indicates that the reaction is not sufficient; while the precursor obtained by microwave-assisted solvothermal reaction with 100% glycerol solvent is mainly cross-linked microspheres. Therefore, the difference in microscopic morphology is mainly related to the difference in viscosity between isopropanol and glycerol.

[0093] Comparative Example 4:

[0094] 100 g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 500 mL of isopropanol and 500 mL of propylene glycol, and the amount of triblock copolymer P123 stabilizer added was controlled to be 0 g and 50 g, respectively. The resulting suspension was placed in a reactor, subjected to microwave-assisted solvent thermal reaction, and kept warm at a reaction temperature of 200 °C for 30 min. After centrifugation or filtration, the suspension was washed three times with distilled water and twice with ethanol to obtain a precursor.

[0095] Fig.13 The results show that when no triblock copolymer P123 stabilizer is added, the precursor obtained is a randomly stacked nanoparticle; while when 50g of triblock copolymer P123 stabilizer is added, the precursor obtained is a micron sphere of uneven size, indicating that the triblock copolymer P123 stabilizer can crosslink and agglomerate the nanoparticles to form a secondary spherical structure during the microwave-assisted solvothermal reaction, but excessive addition of stabilizer will strengthen Oswald ripening, causing the smaller crystals or sol particles in the solute to dissolve and re-deposit on the larger crystals or sol particles. Therefore, the appropriate addition content of the stabilizer in the microwave-assisted solvothermal reaction directly determines the self-assembly of the secondary micron sphere structure and plays an important role in the stability of the uniform micron sphere structure.

[0096] Comparative Example 5:

[0097] 100 g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 500 mL of isopropanol and 500 mL of glycerol, and 20 g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor and subjected to microwave-assisted solvent thermal reaction at 200 °C for 30 min. After centrifugation or filtration, it was washed with distilled water three times and ethanol twice to obtain a brown H 0.93 MoO3 / C precursor; the obtained H 0.93The MoO3 / C precursor was placed in argon plasma, and the calcination temperature was controlled to be 650℃ and 700℃ respectively. The calcination reaction was carried out for 40 min to obtain MoO2 / C series materials.

[0098] Fig.14 The results show that when the temperature range is 500-600℃, pure phase of MoO2 can be obtained, and as the calcination temperature increases, the crystallinity of the material increases; when the temperature is increased to 650℃, MoO2 / C is further carbothermally reduced, and Mo2C mixed phase appears, and MoO2 / Mo2C composite material is obtained; when the temperature is further increased to 700℃, MoO2 / Mo2C / C is further carbothermally reduced, and Mo mixed phase appears, and MoO2 / Mo2C / Mo composite material is obtained. Therefore, in order to obtain pure phase of MoO2, the reaction temperature needs to be controlled below 650℃.

[0099] Comparative Example 6:

[0100] 100 g of commercial MoO3 powder was stirred and dispersed in a mixed solution of 500 mL of isopropanol and 500 mL of glycerol (1:1, volume ratio), and 20 g of triblock copolymer P123 stabilizer was added. The obtained stable suspension was placed in a reactor, and microwave-assisted solvent thermal reaction was carried out at a reaction temperature of 200 °C for 30 min. After centrifugation or filtration, it was washed with distilled water three times and ethanol twice to obtain a brown H 0.93 MoO3 / C precursor; the obtained H 0.93 The MoO3 / C precursor was placed in 15% hydrogen-argon plasma, the calcination temperature was controlled at 400℃ and 700℃, and the calcination reaction was carried out for 40 min to obtain the Mo2C / C series materials.

[0101] Fig.15 The results show that when the temperature is raised to 400℃, the Mo2C phase appears, but there is an impurity phase; when the temperature is further raised to 600℃, the pure Mo2C phase can be obtained; when the temperature is further raised to 700℃, it is still the pure Mo2C phase, and as the calcination temperature increases, the crystallinity of the material increases. Therefore, in order to obtain the pure Mo2C phase, the reaction temperature needs to be controlled to be greater than 400℃.

[0102] The above-mentioned embodiments of the present application are only part of the preferred embodiments of the present application and cannot be used to limit the present application. Without departing from the essence of the present application, any modifications, equivalent substitutions and improvements made by technical personnel in this field are within the scope of protection of the present application.

Claims

1. A method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide, characterized in that: The steps include: S1 MoO3 powder was stirred and dispersed in a mixed solution of monohydric alcohol and polyhydric alcohol, and then triblock copolymer P123 stabilizer was added. The resulting suspension was subjected to microwave-assisted solvent thermal reaction, and then centrifuged or filtered and washed to obtain brown H with a diameter of 1.50-1.60 μm. 0.93 MoO3 / C precursor microspheres; S2: H obtained in step S1 0.93 The MoO3 / C precursor is placed in an argon plasma atmosphere and calcined at a high temperature of 500-600°C for 30-60 min to obtain brown-black MoO2 / C microspheres with a diameter of 1.00-1.10 μm. Alternatively, the H obtained in step S1 0.93 The MoO3 / C precursor is placed in a hydrogen-argon plasma atmosphere and calcined at a high temperature of 500-600°C for 30-60 minutes to obtain dark grey Mo2C / C microspheres with a diameter of 0.75-0.85 μm.

2. The method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide according to claim 1, characterized in that: In the step S1, the monohydric alcohol is selected from at least one of methanol, ethanol and isopropanol, and the polyhydric alcohol is selected from at least one of ethylene glycol and propylene glycol.

3. The method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide according to claim 2, characterized in that: In the step S1, the volume ratio of the monohydric alcohol to the polyhydric alcohol is 1:2 to 2:

1.

4. The method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide according to claim 3, characterized in that: In the step S1, the mass ratio of the added amount of the triblock copolymer P123 stabilizer to the mixed solution of the monohydric alcohol and the polyhydric alcohol is 10 g to 30 g / L.

5. The method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide according to claim 1, characterized in that: In the step S1, the suspension is subjected to microwave-assisted solvent thermal reaction at a temperature of 180 to 210° C. and a heat preservation time of 20 to 40 minutes.

6. The method for reducing molybdenum trioxide to generate molybdenum dioxide or molybdenum carbide according to any one of claims 1 to 5, characterized in that: The hydrogen in the hydrogen-argon plasma atmosphere accounts for 15% of the total amount.

7. Application of the MoO2 / C material and Mo2C / C material prepared by the method of any one of claims 1 to 6 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • High-performance electrochemical capacitor negative electrode material molybdenum dioxide and nitrogen-doped carbon composite material and preparation method and application thereof

    CN110364366A

  • Mo2C and carbon-coated molybdenum-based heterostructure material as well as preparation method and application thereof

    CN114538517A

  • Preparation method for effectively reducing volume expansion rate of molybdenum oxide electrode material and product and application thereof

    CN117497688A

  • Method for obtaining molybdenum dioxide nanoparticles

    RU2767917C1

  • Method for preparing molybdenum oxide nanoparticles

    US20160362303A1

Cited By

  • Tubular cobalt-nitrogen co-doped carbon catalyst with double-mesoporous structure and preparation method of tubular cobalt-nitrogen co-doped carbon catalyst

    CN120054581A